A web-based survey to map the electromyography practice in Brazil - Neto, José Lopes Tabatinga; Basso, Gabriela Ejima Mie; Lima, David Nunes de, Junior; Ferreira, Eduardo Soares; Paula, Denisse Sales; Leitão, Antônio Miguel Furtado; Viana, Antonio Brazil, Júnior; Thomas, Florian Patrick; Gondim, Francisco de Assis Aquino (Arquivos de Neuro-Psiquiatria, 2023)
Background Detailed information about the electromyography practice in Brazil is largely unavailable.Objective To evaluate where and how electromyography is performed in Brazil, as well as regional disparities and the professional and academic credentials of electromyographers.Methods We conducted an internet-based survey of active Brazilian electromyographers. The websites of health insurance companies, professional academies, medical cooperatives, online search engines, and social networks in each Brazilian state were screened and we evaluated the credentials of each electromyographer listed in the Brazilian Federal Medical Board (BFMB) registration website and their online curricula vitae in the Brazilian National Council for Scientific and Technological Development (Conselho Nacional de Desenvolvimento Científico e Tecnológico, CNPq, in Portuguese). We also evaluated the same parameters in a control group of non-electromyographer neurologists randomly matched by geographical distribution and gender.Results We found 469 electromyographers (384 neurologists and 85 non-neurologists), with a male predominance. In total, 81.9% were BFMB-certified neurologists, 49.9%, BFMB-certified clinical neurophysiologists, and 10.4%, BFMB-certified physiatrists. Among the non-neurologists, 48.2% were physiatrists. Most electromyographers practiced in states on the Southern and Southeastern regions of Brazil. When adjusted by population, the Federal District and the states of Mato Grosso do Sul and Goiás presented the highest of eletromyographers density. Electromyographers were not more likely to have current/past academic affiliations.Conclusion In Brazil, electromyography is performed predominantly by neurologists, and half of them are BFMB-certified clinical neurophysiologists. The present study highlights regional disparities and may guide government-based initiatives, for instance, to improve the diagnosis of leprosy and the management of neuromuscular disorders within the Brazilian territory.
Keywords: Brazil; Neurophysiology; Electromyography; Neurology